The effect of conservation measures on the spatial and temporal variation of rocky fish assemblages in the Arrábida Marine Park - Costa, Bárbara Bastos Horta e (2013)
Marine protected areas (MPAs) have been widely proposed for conservation purposes and as a tool for fisheries management. The Arrábida Marine Park is the first MPA in continental Portugal having a management plan, fully implemented since 2009. The main objective of this study was to evaluate the effect of protection measures on rocky reef fish assemblages and target invertebrates through before-after and control-effect (no-take vs. fished areas) underwater visual surveys and analysis of landings trends. Second, we used surveys before, during and after implementation of the management plan to understand fishers‟ preferences for fishing grounds and adaptation to the new rules, and evaluated the reserve effect through analysis of both ecological responses and fishing effort density. Third, we identified the main oceanographic drivers influencing the structure of reef fish assemblages and predicted the community structure for the last 50 years, in light of climatic change. Overall results suggest positive responses in biomass but not yet in numbers of some commercial species, with no effects on non-target species. The reserve effect is reinforced by the increase in landings of commercial species, despite increased fishing effort density in some areas, especially with octopus traps. Fishing grounds are mainly chosen based on the distribution of target species and associated habitats, but distance to port, weather conditions and safety also influence fishers‟ choices. Moreover, different fisheries respond differently to the protection measures, and within each fishery, individual fishers show distinct strategies, with some operating in a broader area whereas others keep preferred territories. Our results also show that wind stress and temperature are the main oceanographic drivers for rocky reef fish assemblages, with tropicalization of assemblages and polewards movements of species over the last 50 years consistent with temperature trends. We believe this study provides significant lessons for marine conservation and management of coastal systems.